The age of consequences : a chronicle of hope and concern - White, Courtney, 1960- (Counterpoint Press, 2015)
Our planet is approaching a critical environmental juncture. Across the globe we continue to deplete the five pools of carbon--soil, wood, coal, oil, and natural gas--at an unsustainable rate. We've burned up half the planet's known reserves of oil--one trillion barrels--in less than a century. When these sources of energy-rich carbon go into severe decline, as they surely will, society will follow. Former archeologist and Sierra Club activist Courtney White calls this moment the Age of Consequences--a time when the worrying consequences of our environmental actions--or inaction--have begun to raise unavoidable and difficult questions. How should we respond? What are effective (and realistic) solutions? In exploring these questions, White draws on his formidable experience as an environmentalist and activist as well as his experience as a father to two children living through this vital moment in time. As a result, The Age of Consequences is a book of ideas and action, but it is also a chronicle of personal experience. Readers follow White as he travels the country--from Kansas to Los Angeles, New York City, Italy, France, Yellowstone, and New England.